If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + -4cx + 5ay + -20cy = 0 Reorder the terms: ax + 5ay + -4cx + -20cy = 0 Solving ax + 5ay + -4cx + -20cy = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4cx' to each side of the equation. ax + 5ay + -4cx + 4cx + -20cy = 0 + 4cx Combine like terms: -4cx + 4cx = 0 ax + 5ay + 0 + -20cy = 0 + 4cx ax + 5ay + -20cy = 0 + 4cx Remove the zero: ax + 5ay + -20cy = 4cx Add '20cy' to each side of the equation. ax + 5ay + -20cy + 20cy = 4cx + 20cy Combine like terms: -20cy + 20cy = 0 ax + 5ay + 0 = 4cx + 20cy ax + 5ay = 4cx + 20cy Reorder the terms: ax + 5ay + -4cx + -20cy = 4cx + -4cx + 20cy + -20cy Combine like terms: 4cx + -4cx = 0 ax + 5ay + -4cx + -20cy = 0 + 20cy + -20cy ax + 5ay + -4cx + -20cy = 20cy + -20cy Combine like terms: 20cy + -20cy = 0 ax + 5ay + -4cx + -20cy = 0 The solution to this equation could not be determined.
| 7(8+x)= | | 9(a+5)=117 | | 5(6-.10)=3(6) | | 81=5/9(f-32) | | (15/7)p=-3 | | 15x^3-12x^2+35x-28= | | -2x^2+84x-441=0 | | 15x-36-x^2=0 | | 5e-4=26 | | 7x+5=3.5x+11 | | 5+10r-2=9r+51-7r | | (-2*1/7)p=-3 | | 7+9n=7n+5 | | 16.5-0.5x=3(2.5x+3) | | 7x+y=4fory | | 3m+12m=75 | | 6x=2*1-4 | | (x/x-2)-2=6/x-2 | | 4p=-44+2p | | 2x-42.6=90 | | z/19=-27 | | w^2+4w-5=0 | | 9/Y+7/Y=4 | | 60x=10y+8 | | -13/4=z | | 3w^2+7w-6= | | 6x+6.7=13.9 | | y=0.5x+4 | | 10x^2-13xy-3y^2=0 | | 2x+27.6=90 | | 9x-14-5x=-10 | | 10x^2+13xy-3y^2=0 |